2020
DOI: 10.1186/s12931-020-01338-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and laboratory findings of 95 cases of 2019 novel coronavirus pneumonia in Wuhan, China: a retrospective analysis

Abstract: Background: Since December 2019, 2019 novel coronavirus pneumonia emerged in Wuhan city and rapidly spread throughout China and even the world. We sought to analyse the clinical characteristics and laboratory findings of some cases with 2019 novel coronavirus pneumonia . Methods: In this retrospective study, we extracted the data on 95 patients with laboratory-confirmed 2019 novel coronavirus pneumonia in Wuhan Xinzhou District People's Hospital from January 16th to February 25th, 2020. Cases were confirmed by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0
19

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(167 citation statements)
references
References 12 publications
6
142
0
19
Order By: Relevance
“…Some literature supported the hypothesis that a little known yet powerful function of neutrophils-the ability to form neutrophil extracellular traps-may contribute to organ damage and death in COVID-19 [19]. Previous studies showed neutrophil count was notably related to disease severity [20,21]. Neutrophil infiltration was noted in two recent reports on the pathological findings from autopsied COVID-19 patients [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…Some literature supported the hypothesis that a little known yet powerful function of neutrophils-the ability to form neutrophil extracellular traps-may contribute to organ damage and death in COVID-19 [19]. Previous studies showed neutrophil count was notably related to disease severity [20,21]. Neutrophil infiltration was noted in two recent reports on the pathological findings from autopsied COVID-19 patients [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…At the beginning of December 2019, a new virus caused an increase in atypical pneumonia at the city of Wuhan in China. The virus was isolated, sequenced and identified as a new type of coronavirus [1]. The virus was called SARS-CoV-2 and the disease associated with that virus was called COVID-19 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing mortality of critically ill patients with COVID‐19 needs early medical intervention, which requires emergency physicians to quickly select severe patients from a large number of patients 8–10 . Thus, rapid and effective assessment of these patients is a crucial task in the emergency department (ED).…”
mentioning
confidence: 99%